History of West Indies cricket - Manley, Michael (Andre Deutsch LondonGB, 1988)
Provides history of West Indies test and international cricket from the first tour of England in 1906 through to 1987. Examines various eras of W.I. cricket such as the Headley years, the three Ws, the Packer years etc. Paints portraits of great W.I. cricketers such as Sobers, Lloyd, and Richards. Discusses cricket's place in West Indian culture and politics. Includes scorecards of all W.I. tests and test averages of W.I. cricketers.